PERANAN FILSAFAT HUKUM DALAM MEWUJUDKAN KEADILAN - Hermoyo, Bambang (Universitas Slamet Riyadi, 2010)
Abstract : The writer in this paper tried to investigated and describe the philosophical thoughts of the role of Law Philosophy in to to realize justice. The formulated hypothesis are : (1) The enforcement of the law materialized the justice and the certainty and insurance in justice, (2) The description of the sense of justice should be in the existing positive law, (3) The philosophy of law represented the search for the deepest meaning of the ultimate result in the law wisdom. Kata Kunci : Filsafat Hukum, rasa keadilan, hukum positif, kebijaksanaan.